Jungian analysis ofMohsin Hamid’s Moth Smoke - Habib, Ayesha; Siddiqa, Ayesha; Marwat, Hidayat Ullah; Khan, Dr. Nijat Ullah (The journal of contemporary issues in business and government, 2021)
This paper aims to unveil the psychological aspects in the character, Darashikoh Shehzad (Daru) of Mohsin Hamid’s novel “Moth Smoke” (2000). It uses the story of Daru, a banker who got fired from his job in the bank. He develops infatuation for his friend Aurangzeb’s (Ozi) wife, Mumtaz, got indulged into drugs and misdeeds hence living a deceitful and wayward life. Jungian theory is applied on Daru by the help of content analysis, bringing out ameliorated comprehension of his affinity with Mumtaz. It concludes that the image of Mumtaz in the psyche of Daru is of an internal woman, which in Jungian terminology known as “Anima”, it is an internal image of a woman imprinted on the psyche of a man. Daru falls for her despite knowing that she is a flare who can extinguish him because if Ozi came to know about their affiliation, it would bring on his indignation on Daru. Mumtaz is irresistible for him as she is his anima and therefore his all efforts to avoid her went futile because once a man finds his anima it is impossible to get rid of her.